Exploring the Impact of Workload and Division of Labor on Health Workers Job Satisfaction at Lepo-Lepo and Mokoau Community Health Centers in Kendari City - Annisa Rodliyah Khotimah; La Ode Saafi; Sartini Risky (Magister Kesehatan Universitas Mandala Waluya, 2026)
Introduction: Low job satisfaction among healthcare workers is caused by various factors, such as heavy workloads and inadequate division of labor. The purpose of this study was to Exploring the Impact of Workload and Division of Labor on Health Workers’ Job Satisfaction at Lepo-Lepo and Mokoau Community Health Centers in Kendari City. Method: This quantitative research used a cross-sectional study design, conducted at the Lepo-Lepo and Mokoau Community Health Centers. The population consisted of all 57 civil servant and non-civil servant nurses at the Lepo-Lepo and Mokoau Community Health Centers, and a sample of 37 nurses was obtained using a proportional random sampling technique. Data collection used a questionnaire. Result: The results of the study on 37 respondents, the majority of whom were less satisfied with their jobs, as many as 22 people (59.5%). The results of the chi-square test of workload (p value 0.000, φ 0.776), division of labor (p value 0.000, φ (0.718). Conclusion: There is a strong relationship between workload and division of labor with Job Satisfaction of Health Workers at Lepo-Lepo and Mokoau Health Centers, Kendari City.